Healthcare-associated infective endocarditis: source of infection and burden of previous healthcare exposure - Mika Halavaara; Kaisa Huotari; Veli-Jukka Anttila; Asko Järvinen (Cambridge University Press, 2023)
Abstract Objective: Prevention of healthcare-associated infective endocarditis (HAIE) is based on characterization of underlying factors. Our object was to describe the source of infection, microbiological etiology, and healthcare-related risk factors for HAIE. Design: Retrospective population-based study. Patients: Adult patients diagnosed with HAIE during 2013-2017 who resided in the study area in Southern Finland with adult population of 0.9 million. Results: Ninety-five HAIE episodes were included. Ten episodes were related to cardiac surgery. Of the remaining 85 episodes, 11 were classified as nosocomial (ie, acquired and diagnosed during ongoing hospitalization) and 74 as non-nosocomial HAIE. Staphylococcus aureus caused 45% of nosocomial episodes, but only 16% of non-nosocomial episodes (P = 0.039). Most common sources of infection in non-nosocomial HAIE were previous hospitalization (24%), dialysis (18%), and urologic procedures (15%). Enterococcus spp. caused 23% of non-nosocomial HAIE, and more than half of them were associated with urologic or gastrointestinal procedures. Two-thirds of the non-nosocomial HAIE patients had recent hospitalization or invasive procedure. We counted previous healthcare-related risk factors for IE and those who had two or more of them had higher in-hospital and one-year mortality. Conclusion: Our study indicates the importance of non-nosocomial acquisition of HAIE and S. aureus as the major pathogen in nosocomial episodes. Enterococcal infections dominate in non-nosocomial cases and further studies are needed to identify patients at risk for enterococcal IE after urological or gastrointestinal procedure.